2022
DOI: 10.3390/biomedicines10071575
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Imaging Derived Predictive Factors of Response Following [177Lu]Lu-PSMA-617 Therapy in Salvage Metastatic Castration-Resistant Prostate Cancer: A Lesion- and Patient-Based Analysis

Abstract: Earlier studies have mostly identified pre-therapeutic clinical and laboratory parameters for the prediction of treatment response to [177Lu]Lu-PSMA-617 in metastatic castration resistant prostate cancer patients (mCRPC). The current study investigated whether imaging-derived factors on baseline [68Ga]Ga-PSMA-11 PET/CT can potentially predict the response after two cycles of [177Lu]Lu-PSMA-617 treatment, in a lesion- and patient-based analysis in men with mCRPC. Included patients had histologically proven mCRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…There are also reports that visceral metastasis can have a negative impact on patients’ disease course [ 9 , 24 ]. However, our results, like some other previous studies [ 8 , 23 ], demonstrated no significant difference between sites of metastasis, at least when compared to other prominent factors such as maximal PSMA uptake. Moreover, PET-based parameters like PSMA-TV and TL-PSMA, although significantly different between groups (in the fourth cycle assessment), did not keep their level of significance when compared to the more significant parameters ( e.g.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…There are also reports that visceral metastasis can have a negative impact on patients’ disease course [ 9 , 24 ]. However, our results, like some other previous studies [ 8 , 23 ], demonstrated no significant difference between sites of metastasis, at least when compared to other prominent factors such as maximal PSMA uptake. Moreover, PET-based parameters like PSMA-TV and TL-PSMA, although significantly different between groups (in the fourth cycle assessment), did not keep their level of significance when compared to the more significant parameters ( e.g.…”
Section: Discussionsupporting
confidence: 76%
“…However, our study expanded on these findings by including a larger sample size and evaluating additional PET/CT parameters such as SUVmax, SULmax, and their ratio to background. In another study by van der Sar et al they also demonstrated a significant correlation between the SUV of the most-avid metastases and response to treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since a possible treatment for advanced disease involves adding 177 Lu-PSMA-617 radionuclide therapy for PSMA-avid disease, prior PSMA-based imaging seems to be in place. Van der Sar et al [ 15 ] reported their experience in utilizing 68 Ga-PSMA-11-PET imaging in 32 CRPC patients receiving two cycles of Lu-PSMA-617 treatment. Although the exact uptake indicating sufficient tracer accumulation is still a matter of debate when a lesion-level analysis was performed, the cut-off values for a minimum specificity of 0.8 were SUV peak 12.7 (sensitivity = 0.44) and SUVmax 15.4 (sensitivity = 0.49), and 80% of non-responding metastatic lesions had lower uptake values.…”
Section: Psma Pet/ct In Metastatic Prostate Cancermentioning
confidence: 99%
“…When assessing radiographic progression at the lesion level in PCa, the choice of imaging biomarker can drastically impact the resulting classification of that disease site. Quantification of burden at the lesion-level can be undertaken using any number of different biomarkers, including SUV max , SUV mean , SUV peak (as recommended by the PERCIST criteria) and volume (which is implicitly incorporated into patient level frameworks such as RECIP 1.0, which requires a whole-body measurement of PSMA-positive tumour volume), among many others 15 , 20 , 24 , 29 . Our study found substantial heterogeneity in lesion-level progression classifications (progressing, stable, and responding) dependent on the imaging biomarker used for assessing response (> 60% of lesions with discordant classifications).…”
Section: Discussionmentioning
confidence: 99%